2019
DOI: 10.1016/j.ijcard.2018.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and the development of atrial fibrillation

Abstract: Background: Chronic obstructive pulmonary disease (COPD) has been associated with atrial fibrillation (AF). More insight into the epidemiology and underlying mechanisms is required to optimize management. Methods: The Rotterdam Study is a large, population-based cohort study with long-term follow-up. Time dependent Cox proportional hazard models were constructed to study the effect of COPD on incident AF, adjusted for age, sex and pack years of cigarette smoking, and additionally stratified according to exacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 53 publications
(83 reference statements)
3
31
0
3
Order By: Relevance
“…We have shown that COPD is associated with an increased risk of peripheral artery disease [332], sudden cardiac death [333] and the development of atrial fibrillation [334]. COPD subjects with frequent exacerbations, with an enlarged left atrium on echocardiography or increased systemic inflammation had a significantly increased risk to develop atrial fibrillation [334]. Since atrial fibrillation is often asymptomatic and is an important cause of (embolic) stroke, this association between COPD-especially during or following acute exacerbations-and atrial fibrillation has implications for clinical practice.…”
Section: Main Results In the Last 3 Yearsmentioning
confidence: 99%
“…We have shown that COPD is associated with an increased risk of peripheral artery disease [332], sudden cardiac death [333] and the development of atrial fibrillation [334]. COPD subjects with frequent exacerbations, with an enlarged left atrium on echocardiography or increased systemic inflammation had a significantly increased risk to develop atrial fibrillation [334]. Since atrial fibrillation is often asymptomatic and is an important cause of (embolic) stroke, this association between COPD-especially during or following acute exacerbations-and atrial fibrillation has implications for clinical practice.…”
Section: Main Results In the Last 3 Yearsmentioning
confidence: 99%
“…In line with this, diabetes has been shown to be associated with an increased risk of stroke, even in younger patients . Other less well‐studied risk factors, such as chronic obstructive pulmonary disease, are also linked to AF, which is probably driven by systemic inflammation …”
Section: Prevalence and Risk Factors Of Atrial Fibrillationmentioning
confidence: 74%
“…9 Other less well-studied risk factors, such as chronic obstructive pulmonary disease, are also linked to AF, 10 which is probably driven by systemic inflammation. 11…”
Section: Prevalence and Risk Factors Of Atrial Fibrillationmentioning
confidence: 99%
“…Our study showed a similar result of a 1.5-fold risk of one-year recurrent IS. One-year noncardioembolic stroke was related to old age, lower high-density lipoproteins, and chronic kidney disease with an HR 1.73 (95% CI: 1.03–2.90) in Japan [ 22 ]. Higher mortality risk was observed in patients with chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%